Caracterización zoométrica y faneróptica del cerdo criollo en cantones de Bolívar y Junín, provincia de Manabí - Anchundia Ordoñez, Jimmy Alejandro (2023)
The objective of this research was to identify the zoometric and phaneroptic characteristics of the Creole pig from the cantons Bolívar and Junín, Manabí province. 16 Creole animals over one year of age were evaluated, 17 zoometric variables, 7 phaneroptic variables and 8 zoometric indices were used, the data were processed with the Excel statistical program, obtaining the following results of zoometric measurements with an average of; BW (kg) 60.26 – 50.55; LCZ (cm) 29.86 – 25.56; ACZ (cm) 14.57 – 11.72; LH (cm) 13.43 – 11.53; AH (cm) 14.00 – 13.44; LGR (cm)21.34 – 15.42; ANG (cm)24.86 – 23.60; ALC (cm) 62.00 – 48.74; ALG (cm) 70.71 – 61.18; ANC (cm) 61.71 – 58.33; LD (cm) 84.71 – 80.78; DDE (cm) 59.00 – 66.56; DBC (cm) 52.29 – 57.52; PTO (cm) 89.00 – 77.89; GWP (cm) 16.00 – 16.22; LO (cm) 19.43 – 14.58; AO (cm) 16.29 – 15.04. Next, with the measurements, the zoometric indices were evaluated in males and females ICF48.64 – 184.08; IF45.02 – 45.16; IPD73.97 – 60.68; PRP 97.24 – 8.02; CI 94.77 – 136.62; IPV 117.72 – 160.63; IMT 18.08 – 55.75; ITO 91.05 – 86.45. From the phaneroptic variables, it was determined that the predominant typology of the Creole pig within the cantons is: black in color, long and short hair type, black and pink mucosa color, having a straight frontonasal profile, with white and black hooves, and the Asian ear type. Therefore, it is concluded that the characteristics of Creole pigs are black, robust and very rare in these cantons.